Failure to Launch: The Endocrine Disruptor Screening Program at the U.S. Environmental Protection Agency - Maffini, Maricel V.; Vandenberg, Laura N. (Frontiers in Toxicology, 2022)
It has been 25 years since the U.S. Congress passed the Food Quality Protection Act of 1996, an amendment to the Food Drug and Cosmetic Act, which mandated that the US Environmental Protection Agency (EPA) test all pesticide chemicals used in food for endocrine disruption. Soon after the law passed, EPA established the Endocrine Disruptor Screening and Testing Advisory Committee (EDSTAC) to provide recommendations to the agency on how its Endocrine Disruptor Screening Program (EDSP) should work. Among them, the committee recommended that EDSP screening should 1) evaluate both human and ecological effects; 2) test for disruption of the estrogen, androgen, and thyroid systems; 3) evaluate pesticide and non-pesticide chemicals; and 4) implement a tiered approach. EPA adopted the recommendations and the EDSP was created in 1998. To date, the EPA has yet to fully implement the law; in other words, it has failed to test all pesticide chemicals for endocrine disruption. Of the small number that have been tested, not a single pesticide chemical has been determined to be an endocrine disruptor, and no regulatory actions have been taken. Here, we review the missed opportunities EPA had to make the EDSP a functional and effective program aimed at protecting human health and the environment. Two reports by the EPA’s Office of Inspector General from 2011 and 2021 provide the framework for our discussion.